Alterations in Proteins and Amino Acids of the Cyanobacterium Anacystis nidulans in Response to Different Inorganic Formulations - Kumar, Gajendra; Singh, Gajendra Pal (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2017)
Anacystis nidulans is a small, rod-shaped, unicellular, colonial, obligatory phototrophic microalga isolated from Sambhar Lake, Jaipur (Rajasthan). To find out the best inorganic composition cultures were grown in five different defined inorganic medium such as Modified BG-11 medium (pH 7.31), BG-11 medium (7.1), CHU-10 (pH 7.65), Zarrouks medium (pH 10.2) and Kratz & Myer medium (pH 9.5) and kept at the temperature of 25 ± 2°C, illuminated with white fluorescent lamps at a light intensity of 2.5 Klux with 12:12 hours light/dark photoperiod in departmental laboratory. Protein content is determined by Bradford assay and qualitatively by SDS-PAGE. Protein expression levels were determined through densitometry. Highest protein and amino acid content were obtained in Modified BG-11 medium as compared to other medium. Two polypeptides of 54.3 and 56.2 kDa were uniquely observed, but the genotype of 35.8 kDa polypeptide was completely degraded under Modified BG-11 inorganic formulation. 35.8, 54.3, 56.2 and 61.8 kDa polypeptides were completely degraded in Zarroukâs as well as Kratz and Myer medium. The expression of some polypeptides of 14.0, 34.1, 42.3, 45.9, 49.5 and 75.0 kDa were greatly reduced and expressed only 1mm level in Zarrouks and Kratz and Myer medium. Quantity of free amino acids maximum was in Modified BG-11 medium and minimum was in the Kratz and Myer Medium. Total 17amino acids were observed in the HPLC chromatogram. No detectable amount of asparagine, glutamine and tryptophan were found throughout the course of the algal life cycle